2001
DOI: 10.1074/jbc.m005547200
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases as Modulators of the Estrogen Receptor Transcriptional Response

Abstract: The estrogen receptor ␣ (ER) is a ligand-dependent transcription factor that plays a critical role in the development and progression of breast cancer, in part, by regulating target genes involved in cellular proliferation. To identify novel components that affect the ER transcriptional response, we performed a genetic screen in yeast and identified RDI1, a Rho guanine nucleotide dissociation inhibitor (Rho GDI), as a positive regulator of ER transactivation. Overexpression of the human homologue of RDI1, Rho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 67 publications
11
60
0
Order By: Relevance
“…4). These findings are in agreement with previous transfection experiments carried out in U2OS cells (Su et al 2001).…”
Section: Rhogdia Enhances Estrogen-mediated Transactivation In U2os Csupporting
confidence: 94%
See 2 more Smart Citations
“…4). These findings are in agreement with previous transfection experiments carried out in U2OS cells (Su et al 2001).…”
Section: Rhogdia Enhances Estrogen-mediated Transactivation In U2os Csupporting
confidence: 94%
“…Likewise, the localization of RhoGDIa in the nucleolus may help to simultaneously sequester RhoGDIa from cytoplasmic GTPases and from ERa and at the same time serve as a storage depot to maintain a pool of nuclear RhoGDIa protein that could interact with ERa and influence gene expression. The ability of RhoGDIa to alter ERa activity was previously reported by Garabedian and coworkers (Su et al 2001), who showed that RhoGDIa enhances ERa, ERb, glucocorticoid receptor and androgen receptor (AR), but not SRF or Sp1, mediated transactivation in transient transfection assays. A subsequent study by this group suggested that RhoGDIa enhances ERamediated transactivation indirectly through its effects on ERa-associated coregulatory proteins (Su et al 2002).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This protein contains a promiscuous binding site that mediates two different interactions, its regulator rho-GDI (rdi1) [50], and the GTPase-activating protein lrg1 [51]. This interface comprises four modules (Fig.…”
Section: Cdc42 Gtpasementioning
confidence: 99%
“…Described signaling cascades resulting in transcriptional activation are as follows: c-Src tyrosine kinase and downstream MAPK, PI3K, and mitogen/ERK kinase-1 (15)(16)(17)(18)(19). Also, monomeric G-protein Rho pathways are involved in ER␣-mediated transcriptional activity * This work was supported, in whole or in part, by National Institutes of Health (20). In the case of mSlo1, a genomic mechanism defines the up-regulation by estrogen-activated ER␣, where ER␣ binds to quasi-perfect EREs in the mSlo1 promoter, a mechanism that may be complemented by Sp1 transcription factor (21).…”
mentioning
confidence: 99%